Caracterização dos efluentes líquidos produzidos no Campus A. C. Simões da Universidade Federal de Alagoas - Cavalcante, Juliana Costa (2017)
Untreated wastewater represents a source of pollution and a risk to the environment and human health. In this scenario, In this scenario, the US Environmental Protection Agency (USEPA) considers that Higher Education Institutions (HEIs) in the development of new technologies are inserted in the group of small units that generate hazardous waste. The A. C. Simoes Campus (CACS) from the Federal University of Alagoas (UFAL) wastewater is generated by diversified teaching and research activities, from restrooms, laboratories, restaurants, cafeterias, the university residence, as well as the University Hospital Professor Alberto Antunes (HUPAA) that results in a sanitary and chemical sewage, since there is no preliminary separation. The aim of this study is to present the results of the physico-chemical characterization, the aerobic and anaerobic biodegradability evaluation and the ecotoxicological evaluation of the wastewater produced in the UFAL campus. The physico-chemical parameters showed the wastewater from the campus had characteristics of typical domestic wastewater, with average values of COD, BOD5,20, N-NTK, N-NH4 and Total Phosphorus of 471.71 mg/L, 416.86 mg/L, 62.08 mg/L respectively. Concentrations of COD, BOD5.20, N-NTK, N-NH4 and Total Phosphorus of 718.92 mg/L, respectively. 400.8 mg/L, 53.84 mg/L, 32.69 mg/L, and 5.75 mg/L. The Cr, Pb, Zn and Cu metals showed values below the emission limits values of the legislation for the discharge of effluents. The effluents from HUPAA, University Restaurant and the final effluent produced in the UFAL campus presented acute toxicity to Artemia franciscana, with CL50 of, respectively, 13.91%, 15.70% and 15.15%. The biodegradability test demonstrated that the effluent generated in the campus UFAL is feasible to be treated biologically, preferably aerobically (efficiency of 92%), however when the anaerobic pathway was used, after the microorganisms adaptation, a COD removal was around 75%.